The effect of operating cash flow, investment cash flow, financing cash flow, gross profit margin, and earnings per share on stock prices of Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) 2018–2021 - Gulo, Hevin Rivaldo; Butar-Butar, Ribka Sari; Sirait, Dita Eka Pertiwi (Journal of Economics and Business Letters, 2024)
The Indonesian economy continues to grow annually. This is marked by the establishment of many state-owned and foreign companies. With so many companies running in Indonesia, it will certainly promote a level of competitive business competition by business operators so that companies need various plans so that they can always survive in the world of business competition and compete to become market leaders in each of same business fields. Operating cash flow is directly related to the operational activities involved in determining net income in a certain period. These activities are obtained from company income related to transactions that affect profits or losses. Cash Flow Report is a type of financial statement that presents a company's cash flow from operating activities and investments. There are 76 samples of companies listed on the IDX. We can see that companies that have the code ULTJ in 2020-2021 saw an increase in cash flow from operating activities by 16. 22% and there was an increase in earnings per share of 15.63%, but the share price decreased by 1.88%. Therefore, the company was in trouble. Likewise, companies that had the ADES code in 2019-2020 experienced a decrease in cash flow from investment activities by 114.86%, but there was an increase in their share price by 39.71%; therefore, the company was in trouble.  Meanwhile, the company code TBLA in the year 2018-2019 saw a decrease in cash flow from financing activities of 67.37% and a decrease in gross profit of 9.03%; however, there was an increase in the share price of 15.03%; therefore, the company was in trouble.